Coach identity leadership behaviours are positively associated with athlete resource appraisals: The mediating roles of relational and group identification. (November 2020) - Miller, Anthony J.; Slater, Matthew J.; Turner, Martin J.
Abstract: Background: There is growing evidence identifying the positive effects of sport and exercise leaders engaging in identity leadership. Yet we have limited knowledge of how identity leadership is associated with athletes' resource appraisals (e.g., self-efficacy) and performance, the underpinning mechanisms that explain such relationships, and changes in relationships across a sporting season. Methods: In Study 1, 412 amateur and professional athletes completed seven questionnaires directly prior to athletic competition in a cross-sectional design. In Study 2, 136 athletes completed seven questionnaires directly before competition, and one questionnaire directly after competition both at the start and the end of the athletic season. Results: In Study 1, relational identification and group identification mediated the positive relationship between identity leadership and self-efficacy, control, approach goals and social support. In Study 2, identity leadership at the start of the season predicted self-efficacy at the end of the season through relational identification. Group identification did not significantly mediate the identity leadership-resource appraisal relationship. Perceived social support at the start of the season predicted greater performance satisfaction at the end of the competitive season. Conclusions: Findings provide evidence that sport coaches' engagement in identity leadership is key to forming a shared social identity, which in turn, is broadly adaptive for stress appraisals and performance satisfaction both cross sectionally and longitudinally. Highlights: Identity leadership by coaches promotes positive appraisals of competitive events. Effects are mediated by athletes' relational and group identification. Identity leadership by a coach promotes positive appraisals of competitive events over time. Received support across a season promotes greater athlete performance satisfaction.